PORGAM CORPORATE SOCIAL RESPONSIBILITY PEMBERDAYAAN TKW PURNA BERBASIS UMKM - Ade Iwan Ridwanullah (Jurnal Inovasi Penelitian, 2020)
Research on Corporate Social Responsibility (CSR) for Empowerment of ex-female migrant worker (TKW Purna) based on UMKM as part of the excellent program of CSR’s Pertamina RU VI Balongan, Indramayu, West Java Province. This activity program is motivated by the conditions of community in Indramayu as the second largest region in Indonesia female migrants worker (TKW) abroad who have also contributed to the number of total female migrant workers (TKW) which has an impact on the high rate of productive unemployment which is not matched by the availability of employment. The research method used is a qualitative descriptive method through interviews, field notes and documentation. The results showed that the empowerment of ex-female migrant worker (TKW Purna) based on UMKM was carried out through mentoring activities, creating Joint Entrepreneur Group (KUB) “Hawa Kreasi”, financial assistantship, p-irt certification and package branding, entrepreneurship management training and marketing activities. The succeeded of these activities program is supported by factors that support activities including: resources, communication, and organizational structures that influence and strengthen each other.